Improved tow-term backpropagation error function with GA-based parameter tuning for classification problem - 256871 Ana Salwa Shafie (Skudai : Universiti Teknologi Malaysia, 2005)
Thesis (Sarjana Sains (Sains Komputer)) - Universiti Teknologi Malaysia, 2005